PENDIDIKAN KARAKTER SECARA TERPADU MELALUI MANAJEMEN BERBASIS SEKOLAH DI SEKOLAH DASAR ISLAM TERPADU INSAN MULIA WONOSOBO (JURNAL ILMIAH TUT WURI HANDAYANI, 2016)
The purpose of this reasearch is to get to know the planning, organisation, execution, surveillance, evaluation gained from the integrated education character through the school-based management in Sekolah Dasar Islam Terpadu Insan Mulia Wonosobo and knowing every obstacle happening and the solution for it. The approach of this research uses qualitative research, the procedure of data aggregation used is observation, interview and documentation. The technique of data analysis forms in qualitative, and the technique of data validity checking done by extending the observation period, continuous observation and source triangulation, triangulation of data aggregation technique and time triangulation. The result of the research gained is : through the integrated character education done according to the school-based management therefore the students of SDIT Insan Mulia Wonosobo have a good character besides achieving either academically or nonacademically and are able to compete in the competition. The school management done by empowering all the existing component by planting character values through (1) planning for the integrated character education committed by the foundation, the principal, the government, the commitee, the teachers and parents, (2) arranging organisation for the integrated character education done through the teaching component, curriculum structure and self-developing programme, (3) execution of the integrated character education committed by integrating Islam values into the subjects, prioritizing qudwah hasanah to create the character of the students, growing the biah solihah in the school climate and environment, involving parents and society to supportfor the sake of education purposes, increasing competention of the educational labours, self-developing activity and accustoming activity, (4) controlling the integrated character education through school-based management done simultaneously by the foundation, the principal, the teachers and parents, (5) evaluating the result of the integrated character education done by the foundation, the principal, the commitee, the teachers and parents which the implementation is done every quarter, semester and one year, (6) the obstacle is usually from the environment where the students live, the solution is to more empower the school cooperation together with parents and society.